Populations of the Sydney rock oyster, Saccostrea glomerata, vary in response to ocean acidification - Parker, L M; Ross, P M; O'Connor, W A (Marine Biology, 2011)
Acidifying oceans are predicted to fundamentally alter marine ecosystems. Over the next century, acute studies suggest that the impacts of climate change on marine organisms and ecosystems may be catastrophic. To date, however, little is known about whether the response of marine organisms varies within a species and whether this provides a potential “adaptive capacity”. Here, we show that selectively bred lines of the ecologically and economically important estuarine mollusc, the Sydney rock oyster Saccostrea glomerata, are more resilient to ocean acidification than the wild populations. When reared at elevated pCO2, we found a 25% reduction in shell growth of the selectively bred population of the Sydney rock oyster, Saccostrea glomerata, compared to a 64% reduction in shell growth of wild populations. This study shows that there are significantly different sensitivities to ocean acidification even within the same species, providing preliminary evidence that selective breeding may be a solution for important aquaculture industries to overcome the future effects of ocean acidification.